CONTINUITY OF FUZZY TRANSITIVE ORDERED SETS - Zeyada, F. M.; Soliman, A. H.; Sayed, N. H. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2012)
In the present paper we introduce and study the continuity for a set equipped with a transitive fuzzy binary order relation which we call a f-toset. Our work is inspired by the slogan: "Order theory is the study of transitive relations" due to S. Abramsky and A.Jung [1].